Encapsulation of chloroquine and doxorubicin by MPEG-PLA to enhance anticancer effects by lysosomes inhibition in ovarian cancer - Shao M (Dove Medical Press, 2018)
Ming Shao,1,* Weitao Zhu,2,* Xianping Lv,1 Qiankun Yang,1 Xin Liu,1 Ying Xie,1 Ping Tang,3 Ling Sun3 1Department of Blood Transfusion, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province 450052, China; 2Department of Clinical Laboratory, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province 450052, China; 3Department of Hematology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province 450052, China *These authors contributed equally to this work Purpose: As the deadliest gynecological malignancy, ovarian cancer ranks as a major cause of disease-related deaths to women worldwide and is treated with transurethral resection or systemic chemotherapy. However, traditional chemotherapeutic drug in antitumor therapy has shown unavoidable limitations, such as poor curative effects, systemic toxicity and development of drug resistance, leading to failure of tumor inhibition and recurrence. This study aims to explore an innovative method to enhance the clinical efficiency of ovarian cancer.Materials and methods: Using MTT assay, the cell viability was detected under different culture systems. Western blot was used to examine the expression of P-gp in doxorubicin-resistant and wild-type A2780/SKOV3 cells. We used confocal to examine the drug concentration under different culture conditions. Also, flow cytometry was used to detect the drug absorption at the determined time points under different culture systems. Using nude mice model, we evaluated the killing efficacy of chemotherapeutic drugs with or without nanoparticle encapsulation. ELISA was used to examine the levels of creatinine, alanine aminotransferase and aspartate aminotransferase in plasma.Results: We found that pretreatment of chloroquine (CQ) as chemosensitizer markedly enhanced the anticancer effects in ovarian cancer. We also provided evidence that CQ efficiently increase the pH value of lysosomes in tumor cells, leading to the reverse of drug sequestration induced by lysosomes. To further improve the pharmacokinetics profiles and avoid the systemic toxicity caused by chemotherapeutic agents, we encapsulated CQ and chemotherapeutic drugs by polymeric nanoparticles methoxy poly(ethylene glycol)-poly(L-lactic acid). Codelivery of CQ and chemotherapeutic agents by nanocarrier revealed enhanced anticancer effects compared with the free drug delivery by tail vein injection. More importantly, accumulated drugs, prolonged drug circulation and reduced organic damages were observed in nanoparticles delivery.Conclusion: Codelivery of CQ and chemotherapeutic drugs by methoxy poly(ethylene glycol)-poly(L-lactic acid) could significantly improve the anticancer effects and might have important potency in clinical applications for ovarian cancer therapy. Keywords: ovarian cancer, chloroquine, cisplatin, MPEG-PLA, nanoparticles